Travel and Tour Management System: Core Transaction 1 (Tour Creation and Configuration, Customer Tour Itinerary Management, Transport Booking, Hotel Reservation, Tour Booking): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Travel and Tours Management System is an integrated and innovative solution designedto handle travel and tour transactions for tour operators, travel agencies, and customers. Thiscomprehensive system provides end-to-end solutions, from hiring new employees andlogistics for equipment to financial expenses and administration. One of the key features ofCore Transaction I management is the creation of unique tour packages, including itineraries,amenities, local hotels and staycations, rental vehicles, and booking pages for clients. Thesystem ensures high-quality services and experiences for clients with reliable serviceproviders.The Travel and Tour Core Transaction I System from the Mblitz Company provides an up-to-date and modern approach to tour creation, management, and booking. The system offers acomprehensive tour management solution for tour operators and travel agencies, includingcreating and configuring tours, managing customer tour itineraries, booking transportation andhotels, and processing tour bookings. New features: web-based & responsive system,tour/itinerary development, hotel/transportation listing, and Gcash payment. Mblitz Travel &Tours improves its manageability and customer accessibility with these enhancements.The Mblitz Company's Travel and Tour Core Transaction I System is a modern and completeplatform that offers a streamlined approach to tour creation, management, and booking. Itsweb-based, flexible interface enables simple tour customization and control of customeritineraries, transportation, and hotel bookings. Customers can easily browse, book, and payusing Gcash, reducing workload for operators and agencies and increasing client retention.The backend efficiently handles reservations and bookings, while the user-friendly interfaceoptimizes operations and improves customer experiences.
Keywords: IT & Management